2005
DOI: 10.1111/j.1600-0722.2005.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Degree of conversion and permeability of dental adhesives

Abstract: The aim of this study was to analyse the extent of polymerization of different adhesive films in relation to their permeability. One adhesive of each class was investigated: OptiBond FL; One-Step; Clearfil Protect Bond; and Xeno III. Adhesive films were prepared and cured with XL-2500 (3M ESPE) for 20, 40 or 60 s. Polymerization kinetic curves of the adhesives tested were obtained with differential scanning calorimetry (DSC) and data were correlated with microhardness. The permeability of the adhesives under t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
210
2
39

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 286 publications
(259 citation statements)
references
References 30 publications
8
210
2
39
Order By: Relevance
“…two-step etch-and-rinse and one-step selfetch systems), the bonded interface lacks a nonsolvated hydrophobic resin coating (Breschi et al, 2008). Any kind of simplification in the clinical application procedure might result in lower bond strengths, incomplete adhesive films polymerization and increased adhesive permeability (Cadenaro et al, 2005). However, various clinical procedures were proposed to optimize bonding and reduce aging, such as extended polymerization time and use of MMPs inhibitors (Breschi et al, 2008;Cadenaro et al), as used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…two-step etch-and-rinse and one-step selfetch systems), the bonded interface lacks a nonsolvated hydrophobic resin coating (Breschi et al, 2008). Any kind of simplification in the clinical application procedure might result in lower bond strengths, incomplete adhesive films polymerization and increased adhesive permeability (Cadenaro et al, 2005). However, various clinical procedures were proposed to optimize bonding and reduce aging, such as extended polymerization time and use of MMPs inhibitors (Breschi et al, 2008;Cadenaro et al), as used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Any kind of simplification in the clinical application procedure might result in lower bond strengths, incomplete adhesive films polymerization and increased adhesive permeability (Cadenaro et al, 2005). However, various clinical procedures were proposed to optimize bonding and reduce aging, such as extended polymerization time and use of MMPs inhibitors (Breschi et al, 2008;Cadenaro et al), as used in this study. Thus, the use of simplified adhesive systems must be chosen with caution, and if possible, accompanied by disinfection protocols such as CHX or other optimized bonding protocols.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between enhanced mechanical properties of dental restorative resins and higher DC has been elucidated [38]. On that account, the increase in the DC of dental adhesives after the prolongation of light exposure time had resulted in improved microhardness and reduced permeability [20]. Regarding the effect of distance of light source on bond strength, it was reported that increasing the distance, had decreased the light intensity, which had negatively affected the shear bond strength of an etch-andrinse adhesive [33].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that the permeability phenomenon could be attributed to the presence of incompletely polymerized acidic monomers within the hybrid layer or dentinal tubules [13,19,20]. Therefore, a low degree of conversion can be associated with increased water sorption, polymer plasticization [21,22], high monomer elution [23] and continuous etching of the tooth substrate [24], resulting in compromised mechanical properties and low bond strength values.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have demonstrated that the physical properties of the adhesive resin may have a profound influence on the resin-dentin bond strengths. Low mechanical property values can compromise the bond strength of the adhesive system [8][9][10][11][12] . Another way, presence of acid monomers may influence on the bondig to dentin and the mechanical properties of adhesive systems [9,10] .…”
Section: Introductionmentioning
confidence: 99%